The engines of our ingenuity : an engineer looks at technology and culture - Lienhard, John H., 1930- (Oxford University Press, 2003)
Millions of people have listened to John H. Lienhard's radio program "The Engines of Our Ingenuity." In this fascinating book, Lienhard gathers his reflections on the nature of technology, culture, and human inventiveness. The book brims with insightful observations. Lienhard writes that the history of technology is a history of us--we are the machines we create. Thus farming dramatically changed the rhythms of human life and redirected history. War seldom fuels invention--radar, jets, and the digital computer all emerged before World War II began. And the medieval Church was a drivi